Calcium pyrophosphate dihydrate crystal deposition of the temporomandibular joint: A case report and review of the literature. Issue 5 (September 2019) - Miyamoto, Isao; Kasamatsu, Atsushi; Hiroshima, Kazuya; Ishida, Nao; Takeuchi, Shin; Takahara, Toshikazu; Ishida, Sho; Yoshimura, Shusaku; Baba, Takao; Saito, Yasuhiro; Iyoda, Manabu; Tanzawa, Hideki
Abstract: Calcium pyrophosphate dihydrate crystal deposition disease (CPPDd) induces arthritis in the surrounding joints with symptoms, such as pain, swelling, and restricted joint movement. CPPDd occurs primarily in the major joints; however, the main manifestation of this disease in the temporomandibular joint (TMJ) is relatively rare. We describe a case of CPPDd in the TMJ of a 54-year-old Japanese woman who was referred to our hospital with the complaints of unpainful swelling in the right TMJ region and restricted mouth opening. Computed tomography (CT) and magnetic resonance imaging (MRI) showed 46 × 42-mm and 27 × 18-mm calcified masses in the right TMJ region. The masses were both outside and inside the mandibular condyle, both of which extended to the skull base. Since we suspected a tumor in the TMJ, the lesion was partially excised for biopsy with the patient under general anesthesia. The microscopic examination showed deposits of calcium pyrophosphate dihydrate crystals, which resulted in a histopathologic diagnosis of CPPDd. According to the suggestion of the neurosurgeon, we removed as much as possible of only the CPPDd tissue on the outside of the mandibular condyle via the preauricular approach to avoid damaging the cranial nerves. The patient was satisﬁed with the postoperative facial symmetry without limited mouth opening. The postoperative follow-up was uneventful.